The Impact of Sustainability Reporting on Profitability in Iraq Stock Exchange: Role of the Transparency as Moderating Variable - Al-Dulaimi, Anmar Adnan Khudhair; Abdulrasool Jaber Al Mamoori, Mohammed; Jawad Al-Khafajy, Eman; Abed, Ahmed Neaah (International Journal of Supply Chain Management, 2020)
Abstract This study has examined moderating impact of transparency on relation between the sustainability reporting disclosure on profitability. The study’s statistical population consisted of listed companies in Iraq Stock  Exchange  for  period 2014 to  2017,  which in this study content of 25 corporation sample was analyzed to assess the level of corporations’ disclosing sustainability reporting through annual reports on  the  activities of the board. Secondary data from annual report of Iraq corporations were used actualize  the  research  objectives  In  this  study.  Panel  data  regression techniques namely fixed  effects  estimation  and  random  effects  estimation  in  addition to pooled Ordinary Least Square  regression  was  carried  out  on  the  secondary data collected from corporations reports. For this purpose, 167 Disclosure indices were analyzed based on Triple Bottom  Line  (TBL)  in  three  economic,  social  and environmental dimensions using a zero-one procedure and rating of each corporation’s disclosing corporate social responsibility was  extracted  to  determine  their level of disclosure. To investigate the association between variables of this research, the level of corporations’ disclosing sustainability reporting independent variable and performance metrics based on accounting data (ROA) as dependent variable are considered. Based on the research results, there is  a  significant  relationship between the level of disclosing corporate  social  responsibility  and  financial performance criteria of corporations based on both accounting data.  Moreover, results of this study can increase individual investors’  confidence  in  investing in companies with stronger corporate  governance.  This  finding  provides  new evidence to the literature as well as for the policy makers to consider on transparency adoption.